Social modulation of androgen levels in male teleost fish - Oliveira, R. F. (2014)
Androgens are classically thought of as the sex steroids controlling male reproduction. However, in recent years evidence has accumulated showing that androgens can also be affected by the interactions between conspecifics, suggesting reciprocal interactions between androgens and behaviour. These results have been interpreted as an adaptation for individuals to adjust their agonistic motivation and to cope with changes in their social environment. Thus, male–male interactions would stimulate the production of androgens, and the levels of androgens would be a function of the stability of its social environment [‘challenge hypothesis’, Gen. Comp. Endocrinol. 56 (1984) 417]. Here the available data on social modulation of androgen levels in male teleosts are reviewed and some predictions of the challenge hypothesis are addressed using teleosts as a study model. We investigate the causal link between social status, territoriality and elevated androgen levels and the available evidence suggests that the social environment indeed modulates the endocrine axis of teleosts. The association between higher androgen levels and social rank emerges mainly in periods of social instability. As reported in the avian literature, in teleosts the trade-off between androgens and parental care is indicated by the fact that during the parental phase breeding males decreased their androgen levels. A comparison of androgen responsiveness between teleost species with different mating and parenting systems also reveals that parenting explains the variation observed in androgen responsiveness to a higher degree than the mating strategy. Finally, the adaptive value of social modulation of androgens and some of its evolutionary consequences are discussed.